The Meaning of "Vepx-i" in Shota Rustaveliʼs "The Man in the Pantherʼs Skin" - Magarotto, Luigi (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2016)
The present work refers to the interpretation of the animal – tiger given in the MPS. According to the author, the name is not related with the modern Georgian tiger.